Catalytic walls and micro-devices for generating hydrogen by low temperature steam reforming of ethanol - Casanovas, Albert (2009)
Ethanol steam reforming (S/C = 3) was effectively performed at low temperature over catalytic wall reactors comprising a wide range of channel dimensions, ranging from conventional monoliths (channel width of 0.9 mm) to semicylindrical microchannels (0.35 mm radius) and to silicon micromonoliths (channel diameter of 3–4 mm). Co3O4 catalyst coatings were successfully prepared inside the channels from in situ thermal decomposition of two-dimensional layered cobalt hydroxide salts and showed a remarkable high homogeneity and mechanical stability. The Si-micromonolithic reactor proved extremely promising for hydrogen production for micro-fuel cell operation. Specific H2 production rates exceeding 50 LN of H2 per mL of liquid and cm3 of reactor were measured for ca. 42% ethanol conversion and residence times in the order of milliseconds.